Improvement of Multipath Routing Flow-based Models for Different Paths Classes - Єременко, О. С.; Tariki, N.; Abdulwahd Mohanad Najm (My University, 2015)
Improvement of multipath routing flow-based models for different paths classes in Telecommunication Network (TCN) was presented. These models are further extension of the well known multipath routing model based on the introduction to the structure of non-linear constraints responsible for calculation the routes of different classes. Among the advantages of proposed model of multipath routing with overlapping by nodes paths, one can distinguish the fact that with the same parameters of security and faulttolerance can be achieved higher performance and quality of service parameters in TCN in a whole.
Keywords: Телекоммуникации; multipath routing; flow-based model; multiflow; non-overlapping paths; overlapping by nodes paths